Elective cardiac surgery during the COVID-19 pandemic: Proceed or postpone? - Shehata, Islam M. (Best Pract Res Clin Anaesthesiol, 2020)
During this coronavirus disease 2019 (COVID-19) pandemic, there is an international call to postpone all elective surgeries. Cardiac surgery carries a combined risk for cardiac patients, who are at risk for higher complications of COVID-19, and healthcare workers. In response to the COVID-19 pandemic, the American College of Surgeons and the American Society of Anesthesiologists recommended a sustained reduction in the rate of new COVID-19 cases for 14 days before the resumption of the elective surgery, but postponing surgery may impact patients’ daily activities and increase the risk the of deterioration of their cardiac condition. We will discuss the risks and benefits of the decision whether to postpone or proceed with elective cardiac surgical procedures during the escalating COVID-19 pandemic considering the specific risk of the cardiac patients, the unique characteristics of the surgery, and the international health system capacity.